The Salary Differential between Male and Female Administrators: Equal Pay for Equal Work? - Sigelman, Lee; Milward, H. Brinton; Shepard, Jon M. (Academy of Management Journal, 1982)
This article presents information on a study which examined the salary differential between male and female administrators in higher education institutions in the United States. The focus of resear...